Peptide-surfactant interactions: Consequences for the amyloid-beta structure - Sandra Rocha (2012)
The conformation of amyloid-beta peptide (A beta) determines if toxic aggregates are formed. The peptide structure by its turn depends on the environment and molecule-molecule interactions. We characterized the secondary structure of A beta-(1-40) in surfactant solutions and interacting with monolayers. The peptide adopts beta-sheet structure in solutions of ionic surfactants at sub-micelle concentrations and alpha-helix in the presence of ionic micelles. Uncharged micelles induce beta-sheets. A beta-(1-40) alters the critical micelle concentration value of the non-ionic surfactant, underlining hydrophobic interactions. At ionic monolayers the peptide forms beta-sheets when its concentration at the surface is high enough. These results suggest that only electrostatic interactions of charged micelles that surround completely the peptide are able to induce non-aggregated a-helix structure.